PENGARUH PENGAWASAN, DISIPLIN DAN KESELAMATAN & KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PT. CITRA AGRO SEJATI KECAMATAN SIMPANG KANAN, KABUPATEN ROKAN HILIR - Mulyadi, Mulyadi; Nuryanti, Nuryanti; Rosnelly, Roesdi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze "The Effect of Supervision, Discipline and Occupational Safety & Health (K3) on Employee Performance of PT. Citra Agro Sejati, Simpang Kanan Subdistrict, Rokan Hilir Regency ”with 44 respondents in the processing division. Data analysis used multiple linear regression analysis method with the help of SPSS (Statistical Package of Social Science) version 20. Based on the hypothesis testing conducted, the results showed that supervision had a significant effect on performance, discipline had a significant effect on performance, and occupational safety & health had a significant effect. on performance. Supervision, Discipline and Occupational Safety & Health (K3) have a significant effect on performance.Keywords : Supervision, Discipline, Occupational Safety & Health (K3), Employee Performance.